Answer :

Given, tn = 4n – 3

First term = t1 = 4 × 1 – 3 = 4 – 3


t1 = 1


Second term = t2 = 4 × 2 – 3 = 8 – 3


t2 = 5


Third term = t3 = 4 × 3 – 3 = 12 – 3


t3 = 9


first three terms to the sequence whose nth term is tn = 4n – 3 is 1, 5 and 9.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any four Maharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

<span lang="EN-USMaharashtra Board - Algebra Papers

Attempt any threeMaharashtra Board - Algebra Papers

Attempt any four Maharashtra Board - Algebra Papers